2021
DOI: 10.3390/membranes11030224
|View full text |Cite
|
Sign up to set email alerts
|

Composite Polymer Anion Exchange Membranes with Sandwich Structure and Improved Performance for Zn–Air Battery

Abstract: In this study, we fabricated a composite polymer anion exchange membrane (AEM) with a sandwich structure. This prepared AEM demonstrated high ionic conductivity (0.25 Scm−1), excellent alkali resistance (8 M KOH), and good mechanical properties (tensile strength of 0.455 MPa and elongation at break of 82.13%). Here, degrease cotton (DC) treated with LiOH/urea aqueous solution was used and immersed into a coagulation bath to form a film. This film was immersed in acrylic acid (AA) monomers, and in-suit polymeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The σ ΟΗ – of S50P50-OH and S50P50-P25-OH membranes was also measured after dipping them in 2 M KOH solution for 24 h, which resulted in σ ΟΗ – values of 113 and 124 mS/cm at 90 °C for S50P50-OH and S50P50-P25-OH membranes, respectively. These values are slightly higher than the values obtained in 1 M KOH–treated samples (Figure A), and this phenomenon of rising OH – conductivity with increasing electrolyte (KOH) concentration is well reported in the literature. , The σ ΟΗ – versus temperature plot for these two samples is shown in Figure S9.…”
Section: Resultssupporting
confidence: 84%
“…The σ ΟΗ – of S50P50-OH and S50P50-P25-OH membranes was also measured after dipping them in 2 M KOH solution for 24 h, which resulted in σ ΟΗ – values of 113 and 124 mS/cm at 90 °C for S50P50-OH and S50P50-P25-OH membranes, respectively. These values are slightly higher than the values obtained in 1 M KOH–treated samples (Figure A), and this phenomenon of rising OH – conductivity with increasing electrolyte (KOH) concentration is well reported in the literature. , The σ ΟΗ – versus temperature plot for these two samples is shown in Figure S9.…”
Section: Resultssupporting
confidence: 84%
“…The tensile strength studies of the optimized AEPEM-GF and AEPEM-70:30 revealed their differences in mechanical properties. 43 As presented in the stress–strain plot (Fig. 2d), AEPEM-GF shows stretchability up to 72% at a tensile stress of about 288 kPa, while AEPEM-70:30 could show only 25% stretchability at a tensile stress of about 60 kPa.…”
Section: Resultsmentioning
confidence: 76%
“…126,128 The polymer networks provide the ductility, exibility, and overall stability (alkaline resistance, CO 2 resistance, chemical stability and thermal stability) to the AEM, accommodating the mechanical requirements of F-ZABs. 129 The controllable water uptake and swelling of the AEM can effectively reduce its structural thickness, 130 thus achieving the lightweight and small-sized design of F-ZABs.…”
Section: Anion Exchange Membrane (Aem)mentioning
confidence: 99%